MENANAMKAN NILAI-NILAI PENDIDIKAN AGAMA ISLAM DI FAKULTAS HUKUM - Suwardi, Suwardi (Ensiklopedia of Journal, 2025)
This study aims to analyze the implementation of Islamic Religious Education values in the Faculty of Law to shape law graduates with integrity and a strong sense of justice. The research employs a qualitative descriptive-analytical method through interviews, observations, and document analysis. The findings indicate that Islamic values have been introduced through curricular and extracurricular activities; however, their integration into legal education has not been fully optimized. Islamic Religious Education plays a strategic role in developing students’ character, ethics, and legal culture. Therefore, strengthening the integration of religious values is essential to support a humane, ethical, and justiceoriented legal education system. Keywords: Islamic Religious Education, Law Faculty, Character Building